Protective Factors on Perpetration of Bullying and Cyberbullying - Guarini, Annalisa; Passini, Stefano; Melotti, Giannino; Brighi, Antonella (Wydawnictwo Naukowe UAM, 2012)
The aim of this study was to describe the prevalence of bullying and cyberbullying perpetration among adolescents and to test the role of demographic (gender, age) and psychosocial variables (self-esteem, loneliness and school climate) associated with these aggressive behaviours. An anonymous questionnaire was ﬁ lled in by 2.326 adolescents from Italian middle and high schools. Results showed that cyberbullying appeared to be less frequent as compared with traditional forms of bullying. Logistic regression analyses revealed a strong continuity between traditional bullying and cyberbullying. Loneliness perceived in the relationships with parents was a very relevant predictor of both forms of bullying (traditional and cyber): i.e. the adolescents who perceived parents as distant were more involved in bullying. A negative relationship with teachers and a low self-esteem about school were other signiﬁ cant risk factors for traditional and cyber perpetration. Besides these common predictors, some differences were found among predictors in traditional bullying and cyberbullying. In fact, males and students of high schools declared to be more involved in the role of a traditional bully than female and younger preadolescents, while gender and age had no predictive role for cyberbullying. A high perception of self-esteem in rela-tionships with peers, a low aversion to loneliness and a perception of unsafety at school triggered cyberbullying, while a high perception of self-esteem in sports activities and of a poor support at school increased the probability of becoming a traditional bully. The results have been discussed focussing on the family and school contexts as crucial relational environments to be considered for intervention programs aimed at preventing not only traditional bullying but also forms of aggression in the virtual world.

Celem tego badania było określenie częstotliwości sprawstwa w zakresie bullyingu i cyberbullyingu wśród adolescentów. Badano związki tego zjawiska z cechami społeczno-demograﬁ cznymi (płeć, wiek) oraz zmiennymi psychospołecznymi (tj. samooceną, samotnością, czy klimatem społecznym szkoły).Anonimowy kwestionariusz został wypełniony przez 2326 adolescentów z wło-skich szkół. Cyberbullying okazał się zjawiskiem rzadziej występującym niż bullying, jednak regresja logistyczna wykazała wyraźnie współwystępowanie tych zjawisk.Samotność doświadczana w relacjach z rodzicami okazała się być predykatorem obu rodzajów przemocy rówieśniczej. Podobnie niska samoocena i złe relacje z nauczycielami korelowały dodatnio z zaangażowaniem w obydwa rodzaje prze-mocy rówieśniczej.Pojawiło się także kilka mniej oczywistych zależności. Starsi nastolatkowie częściej angażowali się jako sprawcy w tradycyjny bullying (w porównaniu z młodszymi chłopcami i dziewczętami). Zmienne te okazały się bez znaczenia przy zaangażowaniu w cyberbullying. Wysoka samoocena w relacji z rówieśnikami, niskie poczucie samotności i postrzeganie szkoły jako niebezpiecznej korelowało z cyberbullyingiem. Z kolei, wysoka samoocena w zakresie kompetencji sportowych i niskie wsparcie w szkole zwiększało prawdopodobieństwo stania się sprawcą tra-dycyjnej agresji. Wyniki potwierdzają, że kluczowe środowiska – rodzina i szkoła – są istotne nie tylko dla zaangażowania w tradycyjną, ale też wirtualną agresję. Powinny one być zatem uwzględniane w programach proﬁ laktycznych dotyczących obydwu tych zjawisk.
Czynniki chroniące i czynniki ryzyka związane z zaangażowaniem w sprawstwo bullyingu i cyberbullyingu
Keywords: cyberbullying; bullying; risk; protective factors; self-esteem; loneliness and school climate; samoocena; klimat szkoły